PERANCANGAN VIDEO PROFILE KOMUNITAS JEPANG WHITE RAVEN - HASBENI, Dr. Syafwandi, M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The community is a group of people who care for each other more than theyshould, where in a community there is a close personal relationship betweenmembers of the community because of the similarity of interest or values. Theprocess of formation is horizontal because it is done by individuals of equalstanding. Community is a social identification and interaction built with variousdimensions of functional needs.White Raven (白 い カ ラ ス Shiroi Karasu) is a community of Japanese cultureand pop-culture lovers founded on the common vision and mission of its members who like various things related to Japan to create a media and container for the JFans.The lack of understanding of the target audience and the lack of optimum mediain delivering information about the Japanese Community's White Raven becamethe main factor of the authors designing the Japanese Community Video Profile of White Raven. The White Raven community promotional media created in theform of audio visual aims to make it easier for people to understand informationabout the Japanese White Raven Community. In addition to this informationdelivery video profile is also supported by several other media that help the main media to introduce the subject to the target audience of posters, stickers, shirts, pins, mugs, x-banners and wall clocks.The methodology used is the 5w + 1h approach of what, who, who, where, why, Using the 5w + 1h theory, all aspects summarized in the Japanese Rural Community Video Profile procession can be packed into audio visual media, Japanese community video profile White Raven can be a medium that has factual information that is effective and communicative to the target audience.Keywords: Video Profile, Japanese Community White Raven.